2018
DOI: 10.1155/2018/1783513
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Enhances Wound Healing in the Rat Palate

Abstract: Introduction Humic acid was previously shown to enhance cutaneous wound healing and show antibacterial properties; however, it has not been used for wound healing in the oral cavity. Thus, the goal of this study was the evaluation of the effect of the humic acid on the healing of excisional wounds in an experimental rat study. Materials and Methods A circular wound on mid-palatal surfaces was made on a total of 77 Wistar rats by using a 3-mm biopsy punch under anesthesia. The animals were divided into 4 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Hammad et al 44 reported that 0.2% chlorhexidine gel showed a very good effect in reducing the wound surface on days 7 and 14 compared to the group to which they applied allantoin. Similar to our study, Calisir et al 24 compared the concentrations of 0.09% saline, 0.05% chlorhexidine, and 80 mg/kg of humic acid, and they found on days 7 and 14 of the trial that the groups with chlorhexidine and humic acid were better at closing the wound surfaces than the groups that received saline. In the same study, it was also found that chlorhexidine and humic acid had similar levels of activity when compared among the groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hammad et al 44 reported that 0.2% chlorhexidine gel showed a very good effect in reducing the wound surface on days 7 and 14 compared to the group to which they applied allantoin. Similar to our study, Calisir et al 24 compared the concentrations of 0.09% saline, 0.05% chlorhexidine, and 80 mg/kg of humic acid, and they found on days 7 and 14 of the trial that the groups with chlorhexidine and humic acid were better at closing the wound surfaces than the groups that received saline. In the same study, it was also found that chlorhexidine and humic acid had similar levels of activity when compared among the groups.…”
Section: Discussionsupporting
confidence: 89%
“…Ji et al 23 conducted a study on rats, and showed that humic acid accelerates the healing of wounds on the surface of the skin. Calisir et al 24 reported that humic acid was effective in closing wounds on the palatal mucosa in rats. Although these results suggest that humic acids may be useful in wound healing in palatal mucosa, there is currently not enough evidence showing the effects of humic acid on wound healing in oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 weeks of humic acid administration the found out statistically significant difference between the saline control and the chlorhexidine gluconate group at the end of three weeks.They observed reduced inflammation and the granulation tissue with constricted mucosal epithelial layer. [24] When the groups were evaluated together in terms of pathological examinations, there was a statistically significant improvement in edema, hemorrhage, PNL, MNL / microglia / macrophage evaluations (p <0.05). In the paraplegia evaluation with the modified Tarlov Scoring, there was a significant improvement in the HA group compared with the control group (p <0.001) (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…HA has been previously demonstrated to enhance the WH process because of its antibacterial, antioxidant, immunomodulatory, and anti-inflammatory properties. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of HA is due to its ability to bind to oxygen reactive. [ 12 ] The promotion function of Nrf2 transcriptions as well as its coding proteins in WH is due to their activities against oxidative stress. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%